Simplifying
-6(5p + 4) + -38 = 2(3p + 5)
Reorder the terms:
-6(4 + 5p) + -38 = 2(3p + 5)
(4 * -6 + 5p * -6) + -38 = 2(3p + 5)
(-24 + -30p) + -38 = 2(3p + 5)
Reorder the terms:
-24 + -38 + -30p = 2(3p + 5)
Combine like terms: -24 + -38 = -62
-62 + -30p = 2(3p + 5)
Reorder the terms:
-62 + -30p = 2(5 + 3p)
-62 + -30p = (5 * 2 + 3p * 2)
-62 + -30p = (10 + 6p)
Solving
-62 + -30p = 10 + 6p
Solving for variable 'p'.
Move all terms containing p to the left, all other terms to the right.
Add '-6p' to each side of the equation.
-62 + -30p + -6p = 10 + 6p + -6p
Combine like terms: -30p + -6p = -36p
-62 + -36p = 10 + 6p + -6p
Combine like terms: 6p + -6p = 0
-62 + -36p = 10 + 0
-62 + -36p = 10
Add '62' to each side of the equation.
-62 + 62 + -36p = 10 + 62
Combine like terms: -62 + 62 = 0
0 + -36p = 10 + 62
-36p = 10 + 62
Combine like terms: 10 + 62 = 72
-36p = 72
Divide each side by '-36'.
p = -2
Simplifying
p = -2